THE COMPILED CATALOGUE OF PHOTOELECTRIC UBVR STELLAR MAGNITUDES IN THE TYCHO2 SYSTEM - Relke, E.; Protsyuk, Yu. I.; Andruk, V. M. (Одеські астрономічні публікації, 2016)
In order to calibrate the images of astronomical photographic plates from the archive of UkrVO was created the compiled catalogue of photoelectric UBVR stellar magnitudes. It is based on: the Kornilov catalogue of 13586 WBVR stellar magnitudes (Kornilov at al., 1991), the Mermilliod catalogue of 68540 UBV stellar magnitudes (Mermilliod, 1991) and the Andruk catalogue of 1141 UBVR stellar magnitudes (Andruk at al.,1995). All original coordinates have the different epoch and equinox. We performed the cross reference of stars from these three catalogues with the Tycho2, UCAC4 and XPM catalogues and created a new photometric catalogue on the epoch and equinox of J2000.0.